68Ga-FAPI PET/CT Improves Therapeutic Strategy by Detecting a Second Primary Malignancy in a Patient With Rectal Cancer. (June 2020) - Chen, Haojun; Zhao, Liang; Ruan, Dan; Sun, Long; Lin, Qin
Abstract : Abstract: A 71-year-old man with pathologically confirmed rectal cancer underwent 18 F-FDG PET/CT before radical operation, which showed multiple nodules with low uptake in bilateral pleura and 1 solitary pulmonary nodule with slight uptake in left lung. The subpleural nodule was diagnosed as benign lesion through the biopsy. 68 Ga-labeled fibroblast-activation-protein inhibitor PET/CT was performed for further evaluation, which showed low uptake in bilateral subpleural nodules but focally increased uptake in the nodule of left lung. This nodule was found to be a primary lung adenocarcinoma by the CT-guided biopsy. A diagnosis of rectum and lung double primary malignancies was finally made.